Buzz boy and fly guy - Arnold, Tedd (New York : Scholastic, 2010)
The excitement is jam packed in Fly Guy's newest episode which features a comic book within the story. Buzz and Fly Guy are superheroes! The dynamic duo must battle a fiery dragon and a band of pirates. Will Fly Guy and Buzz Boy defeat their enemies and save their home? Find out in this amazing early chapter book.